Intraocular Risk Factors in the Primary Formation of Diabetic Macular Edema in Patients with Diabetes Mellitus Type II - M. V. Pshenichnov; O. V. Kolenko; E. L. Sorokin; Yu. E. Pashentcev (Oftalʹmologiâ, 2019)
Purpose. Revealing of the intraocular risk factors in the diabetic macular edema (ME) formatis in diabetes mellitus type II (DM2). Patients and methods. A 3.5-year research of 80 patients (160 eyes) with DM2 without signs of ME at the beginning of the research was performed. The main group consisted of 46 patients with ME symptoms on one or both eyes during the research period, the comparison group included 34 patients without ME symptoms to the end of the research. The initial ocular characteristics were retrospectively compared in groups. Results. The mean value of the axial lengths (AL) in the eyes of the main group was 23.12 ± 0.75 mm compared to 23.82 ± 0.62 mm in the comparison group (significant difference, p < 0.01). AL was less than 23.5 mm in 66 % eyes in the main group and only in 22 % of the eyes in the comparison group (p < 0.01). The mean value of the initial macular retina volume in the main group was significantly higher than in the comparison group — 7.51 ± 0.22 mm3 and 7.21 ± 0.12 mm3, respectively (p < 0.01). Initial background diabetic retinopathy (DR) was noted in 73 % eyes in the main group, which significantly differed from the comparison group, where this index was noted only in 13 % of the eyes (p < 0.01). Conclusion. Significant ocular risk factors for the formation of ME in patients with DM2 are: the initial macular retina volume more than 7.3 mm3, the value of the AL less than 23.5 mm; the initial background DR. The use of the detected morphometric parameters of eye and retina in combination with an adequate assessment of the risk factors in human organism makes it possible to assume a high risk of the primary formation of diabetic ME in patients with DM2 with high degree of probability.